Programma: Juan de Marcos González and the 15 piece Afro-Cuban All Stars live in concert in de Melkweg - Piza, Christina, (1998)
Programma: Juan de Marcos González and the 15 piece Afro-Cuban All Stars live in concert in de Melkweg.